Giant genital seborrheic keratosis: A case report and review of the literature (Indian Journal of Case Reports, 2020)
Seborrheic keratosis (SK) of the skin is a quite common lesion characterized by epithelial proliferation. However, its occurrence in genitalia can grossly be mistaken for genital warts and can only be confirmed on histology. We, hereby report the case of a 44-year-old gentleman who presented with large polypoidal growth in the pubic region. Histopathology confirmed it to be giant genital SK.